2021
DOI: 10.1308/rcsann.2021.0075
|View full text |Cite
|
Sign up to set email alerts
|

What is the current practice for managing patients with chronic limb-threatening ischaemia in vascular surgery services? A survey of UK vascular surgeons

Abstract: Introduction The Vascular Society of Great Britain and Ireland (VSGBI) Peripheral Arterial Disease Quality Improvement Framework (PAD QIF) stipulates targets for managing patients with chronic limb-threatening ischaemia (CLTI); however, it is unknown whether these are achievable. This survey aims to evaluate contemporary practice for managing CLTI in the UK. Methods A questionnaire was developed in conjunction with the VSGBI to survey the management of CLTI and canvass opinions on the PAD QIF. The survey was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The outpatient management for patients with CLTI is notoriously challenging, however, with a recent UK survey demonstrating that only 14.3% of centres provide an outpatient consultation within the seven-day referral target. 24 The success of our outpatient clinics relied on the streamlining of patient care, with individuals undergoing a “one stop” clinic that provided assessment and investigations. Additionally, all patients awaiting intervention were routinely swabbed for COVID-19 and methicillin-resistant Staphylococus aureus to facilitate the use of day case angiogram slots and admission for open surgery procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The outpatient management for patients with CLTI is notoriously challenging, however, with a recent UK survey demonstrating that only 14.3% of centres provide an outpatient consultation within the seven-day referral target. 24 The success of our outpatient clinics relied on the streamlining of patient care, with individuals undergoing a “one stop” clinic that provided assessment and investigations. Additionally, all patients awaiting intervention were routinely swabbed for COVID-19 and methicillin-resistant Staphylococus aureus to facilitate the use of day case angiogram slots and admission for open surgery procedures.…”
Section: Discussionmentioning
confidence: 99%
“…CLTI is associated with an increased risk of major limb amputation and mortality2–4 and urgent treatment is required for an optimal prognosis. However, studies examining the care pathway from first symptom to intervention have described how delays can occur at each stage of the process,5 starting with the identification and referral of patients with CLTI6 and also at the time of assessment by vascular services 7. To avoid these, organisations have introduced various initiatives, such as regular ‘hot clinics’ (which are for emergency referrals only) and streaming patients to specific services such as podiatry.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies examining the care pathway from first symptom to intervention have described how delays can occur at each stage of the process, 5 starting with the identification and referral of patients with CLTI 6 and also at the time of assessment by vascular services. 7 To avoid these, organisations have introduced various initiatives, such as regular ‘hot clinics’ (which are for emergency referrals only) and streaming patients to specific services such as podiatry. However, this increases the complexity of the care pathway and there is limited evidence for services to draw on when considering how to organise vascular services so that they meet the needs of the local population and ensure patients with CLTI have rapid access to endovascular or open surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, outpatient endovascular revascularization has become the main option for arterial repair in the United States of America (USA) where the Outpatient Prospective Payment System significantly promotes the shift from inpatient to outpatient settings [13]. However, outpatient setting for LEAD remains low elsewhere [14], notably in France where the proportion of outpatients average 5% and stable since 2016. Some studies showed that procedural and postoperative complications of endovascular revascularization within 30 days of surgery occur in 10% to 13% of the patients [15,16].…”
Section: Introductionmentioning
confidence: 99%